REPRESENTATION OF SOCIAL CLASS IN FILM (Semiotic Analysis of Roland Barthes Film Parasite) - Vicky Dianiya (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Social class differences have been formed long ago which can identify people's identities which are usually measured based on economic status. This class difference is depicted in Bong Joon-ho's Parasite film, telling of two families of different classes. The Kim family as a lower class and vice versa Mr. Park as the upper class. The core theme of the film Parasite is that of realistic drama about class domination which can also be seen around us. The paradigm used is critical interpretative, so researchers not only criticize but also make interpretations related to this Parasite film. In the analysis phase, this study uses Roland Barthes's semiotic analysis, which are signs in the form of words, images, sounds, movements and objects that are analyzed based on three things, namely parsing data based on the connotation, denotation and myths contained in the Parasite film scene. . Furthermore, representations produced through objects or images can produce meaning or processes that we understand or relate them to a meaning. Based on the first analysis of the film industry, Parasite Films are not included in the logic of most cultural industries but still succeed in penetrating the international market. Then, at the stage of representing social class markings in the film Parasite, it is found that there are at least five main points, namely: ease of life, fashion, boundaries, body odor, and color. Thus, the description of social class representation in the film Parasite is perfect both in its scenes, properties, and cinematography.